Pengaruh Green Marketing dan Product Knowledge Terhadap Brand Preference - Haidi, Avia Rosyada; Juwita, Himmiyatul Amanah Jiwa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to investigate the effect of green marketing and product knowledge on brand preference for 100% Aqua Recycle Life products in the Greater Jakarta area. The type of research used is explanatory research with a non-probability sampling approach. Data were obtained from 120 respondents who are 100% consumers of Aqua Recycle Life products and represent the population of the Greater Jakarta area. The variables studied include green marketing, product knowledge, and brand preference. Green marketing is measured through consumer perceptions of environmentally friendly marketing efforts carried out by 100% Aqua Recycle Life. Product knowledge is measured through consumer understanding of the attributes and benefits of 100% Aqua Recycle Life products. Brand preference is measured by looking at consumers' preferences and willingness to choose Aqua Recycle Life 100% compared to other bottled water brands. Data analysis was performed using multiple linear regression techniques to examine the relationship between the independent variables (green marketing and product knowledge) and the dependent variable (brand preference). The results of the study show that green marketing and product knowledge each significantly influence brand preference for Aqua Recycle Life 100% products in the Jabodetabek area. Abstrak Penelitian ini bertujuan untuk menginvestigasi pengaruh green marketing dan pro-duct knowledge terhadap brand preference pada produk Aqua Recycle Life 100% di wilayah Jabodetabek. Jenis penelitian yang digunakan adalah explanatory research dengan pendekatan nonprobability sampling. Data diperoleh dari 120 responden yang merupakan konsumen produk Aqua Recycle Life 100% dan mewakili populasi wilayah Jabodetabek. Variabel yang diteliti meliputi green marketing, product knowledge, dan brand preference. Green marketing diukur melalui persepsi konsumen tentang upaya pemasaran yang ramah lingkungan yang dilakukan oleh Aqua Recycle Life 100%. Product knowledge diukur melalui pemahaman konsumen tentang atribut dan manfaat produk Aqua Recycle Life 100%. Brand preference diukur dengan melihat preferensi dan kesediaan konsumen untuk memilih Aqua Recycle Life 100% dibanding merek air minum dalam kemasan lainnya. Analisis data dilakukan menggunakan teknik regresi linear berganda untuk menguji hubungan antara variabel independen (green marketing dan product knowledge) dengan variabel dependen (brand preference). Hasil penelitian menunjukkan bahwa green marketing dan product knowledge yang masing-masing secara signifikan mempengaruhi brand preference pada produk Aqua Recycle Life 100% di wilayah Jabodetabek.